2019
DOI: 10.1101/792796
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Daughterless, theDrosophilaorthologue of TCF4, is required for associative learning and maintenance of synaptic proteome

Abstract: Mammalian Transcription Factor 4 (TCF4) has been linked to schizophrenia and intellectual disabilities like Pitt-Hopkins syndrome (PTHS). Here we show that similarly to mammalian TCF4, fruit fly orthologue Daughterless (Da) is expressed in the Drosophila brain structures associated with learning and memory, the mushroom bodies. Furthermore, silencing of da in mushroom body neurons impairs appetitive associative learning of the larvae and leads to decreased levels of the synaptic proteins Synapsin (Syn) and dis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Interestingly, a study with Drosophila demonstrated that silencing of TCF4 orthologue Da resulted in synaptic and locomotor impairments (Tamberg et al, 2020). These results highlight the important conservation of TCF4 function in several species, especially regarding neurodevelopment.…”
Section: Ndd‐associated Multifactorial Disordersmentioning
confidence: 99%
“…Interestingly, a study with Drosophila demonstrated that silencing of TCF4 orthologue Da resulted in synaptic and locomotor impairments (Tamberg et al, 2020). These results highlight the important conservation of TCF4 function in several species, especially regarding neurodevelopment.…”
Section: Ndd‐associated Multifactorial Disordersmentioning
confidence: 99%
“…For the ectopic overexpression in Drosophila , the two-component Gal4-upstream activating sequence (UAS) system is widely exploited (43). We chose the 30Y-Gal4 driver line with specific expression in the Drosophila mushroom body previously shown to be capable to affect also the negative geotaxis (44). For the overexpression we used UAS-APP.Aβ42.D694N.VTR responder line expressing human Aβ with an Iowa mutation from familial AD patients, D23N.…”
Section: Resultsmentioning
confidence: 99%
“…First, we showed that PTHS patient-derived neurons have a reduction in excitatory synapse density (Figure 2G-J; Figure 4E, F), a phenotype that was previously reported in the cortex and hippocampus of two different PTHS mouse models 13 ,54 . Similarly, disruption of Da, the TCF4 orthologue in drosophila, led to decreased levels of the synaptic proteins synapsin and disc large 1 55 . Secondly, we observed a significant reduction in the frequency and amplitude of sEPSCs, which was consistent with synaptic density measurements (Figure 2A-C; Figure 5G-I).…”
Section: Tcf4 Regulates Synaptic Development and Functionmentioning
confidence: 98%